FOREIGN EXPERIENCE OF ATTRACTING CITIZENS TO PUBLIC ASSISTANCE IN THE FIGHT AGAINST CRIME (Ustozlar uchun, 2026)
The article analyzes the experience of the police of foreign countries in attracting citizens to publicly assist in the fight against crime.